PENDAMPINGAN PEMILIHAN MEREK, PENTINGNYA MEREK DAN NILAI YANG DIHASILKAN MELALUI MEREK" BAGI PELAKU UMKM DI DESA LAU BAKERI, KECAMATAN KUTALIMBARU, KABUPATEN DELI SERDANG, SUMATERA UTARA - Erwansyah Erwansyah; Rintan Saragih; Truly Okto H. Purba (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Small Micro and Medium Enterprises (MSMEs) is an important sector that contributes to the Indonesian economy. The existence of MSMEs is able to open up opportunities for job creation. The expected output from the existence of MSMEs is an increase in people's welfare and a decrease in the unemployment rate. Lau Bakeri village located in Kutalimbaru sub-district, Deli Serdang district is a village located in North Sumatra province where most of the population work as entrepreneurs (SME actors). Along with the role of MSMEs in the development and improvement of the Indonesian economy, on the one hand MSMEs have various problems. One of them is the absence of a brand on the products or services produced by MSME actors in Lau Bakeri village. This service activity focuses on assisting in brand selection, explaining the importance of brands and brand building strategies. This is important because the brand is the identity of a product, service, SMEs. The goal is that the products/services produced by the MSMEs in Lau Bakeri village have a good identity/image in the community, are widely known by the community, assist the promotion process, generate value, and will have a competitive advantage. The output is an increase in the welfare of MSME actors in Lau Bakeri village.